2017
DOI: 10.29312/remexca.v7i8.93
|View full text |Cite
|
Sign up to set email alerts
|

Rendimiento de grano y características fenotípicas de maíz: efecto de ambiente y dosis de fertilización

Abstract: El maíz es la principal fuente de alimento y es el cultivo que mayor superficie ocupa en México. En el estado de Guerrero existe gran diversidad de regiones agroecológicas que se distinguen por su altitud, temperatura, tipo de suelo, distribución de lluvias, donde los agricultores siembran híbridos, variedades y poblaciones nativas de maíz bajo condiciones de riego y temporal. El objetivo del presente trabajo fue examinar el efecto de diferentes dosis de nitrógeno y fósforo, en características fenotípicas y re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
0
0
Order By: Relevance
“…The average plant height (AP) was 250 cm and fluctuated from 188.6 to 275.6 cm, results similar to those reported by Shelton and Tracy (2013); Manjarrez et al 2014; Gómez et al (2016). Several researchers consider it important to measure plant height in maize to explore genetic diversity between plants (Nuñez et al, 2015).…”
Section: Results Analysis Of Variance and Comparison Of Meanssupporting
confidence: 65%
“…The average plant height (AP) was 250 cm and fluctuated from 188.6 to 275.6 cm, results similar to those reported by Shelton and Tracy (2013); Manjarrez et al 2014; Gómez et al (2016). Several researchers consider it important to measure plant height in maize to explore genetic diversity between plants (Nuñez et al, 2015).…”
Section: Results Analysis Of Variance and Comparison Of Meanssupporting
confidence: 65%
“…Barrios et al (2016) also reported that excess n accumulates in leaf tissues, saturating the N absorption capacity of the crop, resulting in a poor root system, soft tissue, weak plants, delayed production, and lower yields. Gómez et al (2016) indicated that 200 kg.ha -1 of n were required to obtain maximum grain yield; however, with the application of 90 kg.ha -1 of P, they obtained higher values in plant and ear height, ear health and grain yield. However, there are studies (Guo et al, 2016) indicating the case of the loess plateau of China where a potential yield of 98 to 108 % was achieved; varying the optimum dose of N from 207 to 222 kg.ha -1 with a ratio of 65 to 80 kg of grain/kg of N applied.…”
Section: Resultsmentioning
confidence: 96%